Physics and Metaphysics: notes on the poetic spirit of Blake and Whitman - Botero, Manuel José (Estudios Ingleses de la Universidad Complutense, 2013)
Throughout this article I would like to propose, in sort of a progressive way, a relationship between William Blake´s Poetry and Walt Whitman´s Poetry. I do not intend, of course, to relate the totality of the works of either poet; I´ll just focus on one issue that becomes an evolutive tie between both poetic universes: the metaphysical issue. The relationship finds its base at one same epistemological source, that one exposed by Hegel in his philosophy.